Accuracy of laboratory tests collected at referring hospitals versus tertiary care hospitals for acute stroke patients - Thanin Lokeskrawee (2019)
© 2019 Lokeskrawee et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background The standard treatment of acute ischemic stroke patients is thrombolytic therapy within 60 minutes of a patient’s arrival in stroke center hospitals. Based on the policy of the Lampang Referral System Committee, blood samples of suspected stroke patients need to be collected before transfer to the stroke center (Lampang Hospital). It was still questionable as to whether these blood samples are valid for clinical use and the present study aimed to confirm or deny their validity. Methods A diagnostic study was conducted from June 2015 to May 2016. After exclusion, 340 patients were deemed eligible for analysis. Blood samples were collected just before normal saline infusion at referring hospitals and stored in blood collecting tube boxes set during transportation. At the stroke center, informed consents was requested, blood samples were re-collected to serve as a ‘gold standard’. Prothrombin time (PT), international normalized ratio (INR), activated partial thromboplastin time (aPTT), platelet count, hemoglobin (Hb), hematocrit (Hct), blood urea nitrogen (BUN), and creatinine (Cr) were compared using paired t-tests. Binary regression was used to analyze for accuracy (%) to adjust for extraneous influences and was presented by modified Bland-Altman plots. Results The laboratory results of referring hospitals vs. the stroke center were: PT, 12.4±3.2 vs. 12.5±3.0 sec; INR: 1.0±0.3 vs. 1.0±0.3; and platelet count: 239.8±77.1 vs. 239.8±74.8 (x103/μL). The adjusted accuracy of the PT, INR, and platelet counts were 96.8%, 96.8%, and 95.3% respectively. Conclusion Laboratory tests from referring hospital were determined to be valid. Blood samples should thus be collected at referring hospitals in order to avoid unnecessary blood collection at the stroke center.